2017
DOI: 10.1111/1744-9987.12612
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dry Eye Using Anterior Segment Optical Coherence Tomography in Patients With End‐Stage Renal Disease Undergoing Hemodialysis

Abstract: The aim of the present study was to evaluate dry eye parameters with conventional tests and tear meniscus with Anterior Segment Optical Coherence Tomography (AS-OCT) in patients with end-stage renal disease (ESRD). Thirty-eight ESRD patients undergoing hemodialysis, and 40 healthy individuals were enrolled. An ocular surface disease index questionnaire (OSDI) was administered. Before conventional dry eye tests, tear meniscus were evaluated using AS-OCT. After a complete ocular examination, Schirmer and break-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…It was further noted in the present study that, consistent with most other studies, Schirmer test and TBUT results decreased after HD 3 . Ebana Mvogo et al found that 27.1% of HD patients developed lacrimal hyposecretion 21 ; whereas Kal et al found that tear meniscus depth, tear meniscus area, and tear meniscus height were lower in patients with ESRD 10 . Anbar et al found that basal tear secretion and tear film stability were lower, whereas dry eye symptoms such as itching and redness were more common among children with ESRD.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It was further noted in the present study that, consistent with most other studies, Schirmer test and TBUT results decreased after HD 3 . Ebana Mvogo et al found that 27.1% of HD patients developed lacrimal hyposecretion 21 ; whereas Kal et al found that tear meniscus depth, tear meniscus area, and tear meniscus height were lower in patients with ESRD 10 . Anbar et al found that basal tear secretion and tear film stability were lower, whereas dry eye symptoms such as itching and redness were more common among children with ESRD.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with corneal calcification, the mean TBUT was 8.0 ± 3.1 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) seconds when compared to the patients with no corneal calcification (P = .036). In patients with corneal calcification, the Schirmer values of the patients were significantly lower when compared to the patients with no corneal calcification.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations